The Relationship between Total Oil Content in Sediment and the Abundance of Benthic Diatoms in the Waters of Pangkalan Jambi, Bengkalis, Riau - Jihan Fitri Muthiah Rahmah; Irvina Nurrachmi; Sefni Hendris (Fakultas Perikanan dan Kelautan Universitas Riau, 2026)
The research was conducted in December 2025 in the waters of Pangkalan Jambi. The purpose of this research was to analyze the total oil content in sediments, calculate the abundance of benthic diatoms, and explain the relationship between the total oil content in sediment and the abundance of benthic diatoms. The research uses a survey method; three sampling stations with three replications in each station were surveyed. The results showed that the average oil concentration in sediments exceeded the thresholds set by the Department of Water Resources Quality Assurance/Quality Control Program and the Australian and New Zealand Environment and Conservation Council. The results of the calculation of the abundance of benthic diatoms ranged from 2196.14 ind/cm2 to 3362.84 ind/cm2. The highest abundance is around small ports, while the lowest abundance is around the river mouth. Based on simple linear regression, the relationship between sediment oil content and benthic diatom abundance was y = 8281.7 – 1.1367x, with a coefficient of determination (R2)= 0.875 and a correlation coefficient (r) = 0.935. The value of r states a moderate relationship with a constant value b, which is negative, indicating that the higher the oil content, the lower the abundance of benthic diatoms in sediments.